Z-Theory, Foundation and Frame - Zade, Allan (Journal of Education and Vocational Research, 2014)
Despite the fact that Z-Theory was published few years ago (2011), many questions arise until today about nature of the theory, its cause and reason. This article is dedicated to answering key questions of the theory, to lift the veil of â€œmysteryâ€ that surrounds the theory for many centuries and keeps the human mind incompatible with Z-Theory.